2009
DOI: 10.1016/j.socscimed.2008.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Life-course socioeconomic positions and subclinical atherosclerosis in the multi-ethnic study of atherosclerosis

Abstract: A major limitation of past work on the social patterning of atherosclerosis has been the reliance on measures of neighborhood or individual-level socioeconomic position (SEP) assessed at a single point in time in adulthood. Risk of chronic disease is thought to accumulate throughout the life-course, so the use of a measure for a single point in time may result in inaccurate estimates of the social patterning of subclinical disease. Using data from the US Multi-Ethnic Study of Atherosclerosis (MESA), we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 53 publications
9
86
2
1
Order By: Relevance
“…However, many of these studies used limited SEP measures, subclinical markers, or relatively smaller or nonAfrican American sample. 2,17,[22][23][24]32 Adult family income also significantly predicted LVH and PAD after adjustment for age and sex. In another recently published study, investigators found that prevalent diabetes was significantly higher in lower vs high SEP African Americans with associations persisting after risk factor adjustment, which is similar to the relationships between LVH with income and PAD with education.…”
Section: Sep and Subclinical Disease: The Jhs -Deere Et Almentioning
confidence: 95%
See 2 more Smart Citations
“…However, many of these studies used limited SEP measures, subclinical markers, or relatively smaller or nonAfrican American sample. 2,17,[22][23][24]32 Adult family income also significantly predicted LVH and PAD after adjustment for age and sex. In another recently published study, investigators found that prevalent diabetes was significantly higher in lower vs high SEP African Americans with associations persisting after risk factor adjustment, which is similar to the relationships between LVH with income and PAD with education.…”
Section: Sep and Subclinical Disease: The Jhs -Deere Et Almentioning
confidence: 95%
“…1,12,13 Childhood and adult SEP independently and jointly contribute to an increased prevalence of CVD risk factors, subclinical disease, and CVD disparities. [14][15][16][17][18][19][20][21] Prior work has also shown that lower cumulative life course SEP was associated with increased prevalence of subclinical CVD 17,[22][23][24] among relatively smaller or non-African American samples.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This scarring can result in thickening and stiffening of the vascular wall, with consequent narrowing of the vascular lumen. 296 The consequences of these changes include increased blood pressure (especially diastolic pressure) and reduced blood flow, as well as an increased risk of thrombosis.…”
Section: Allostatic Load: Chronic Stress Response and Systemic Inflammentioning
confidence: 99%
“…Further, childhood disadvantage has been treated as static, rather than as a dynamic process involving stability and change over time (e.g. Lemelin et al, 2009;Pudrovska & Anikputa, 2013;Walsemann, Ailshire, Bell & Frongillo, 2012), and its effects rarely compared across health outcomes.…”
Section: Introductionmentioning
confidence: 99%